Mechanical characterization of impact resistance by pendulum tensile test on PETG and PA6 thermoplastics (2018)
This article presents the results of the mechanical characterization of the impact resistance of PETG and PA6 thermoplastic polymers. This type of polymer is being widely used in industrial applications and the characterization of its mechanical properties is a subject of great academic and industrial interest. The impact pendulum technique has been used as the most widely known. The tests have been carried out under different conditions and varying the greatest number of parameters in order to obtain data that allow a rigorous characterization of these materials.